2016
DOI: 10.1515/sagmb-2015-0055
|View full text |Cite
|
Sign up to set email alerts
|

MDI-GPU: accelerating integrative modelling for genomic-scale data using GP-GPU computing

Abstract: Abstract:The integration of multi-dimensional datasets remains a key challenge in systems biology and genomic medicine. Modern high-throughput technologies generate a broad array of different data types, providing distinct -but often complementary -information. However, the large amount of data adds burden to any inference task. Flexible Bayesian methods may reduce the necessity for strong modelling assumptions, but can also increase the computational burden. We present an improved implementation of a Bayesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…One approach (Zhang et al, 2013) uses super k-means clustering of an integrated data matrix to identify modules. Another approach, MDI (Kirk et al, 2012; Mason et al, 2016) uses a Bayesian model to capture relationships between gene sets. When the three methods were run using the most variable features from each dataset, we found that MDI and super k-means do not enrich for PPIs at the same level as MAGNETIC for raw networks as well as networks not used in the construction of MAGNETIC (Figure S3a-e, see implementation of related approaches section).…”
Section: Star Methodsmentioning
confidence: 99%
“…One approach (Zhang et al, 2013) uses super k-means clustering of an integrated data matrix to identify modules. Another approach, MDI (Kirk et al, 2012; Mason et al, 2016) uses a Bayesian model to capture relationships between gene sets. When the three methods were run using the most variable features from each dataset, we found that MDI and super k-means do not enrich for PPIs at the same level as MAGNETIC for raw networks as well as networks not used in the construction of MAGNETIC (Figure S3a-e, see implementation of related approaches section).…”
Section: Star Methodsmentioning
confidence: 99%
“…Bayesian inference was performed using MCMC (see ref. 55 for further details on inference and modelling) as implemented in the MDI-GPU software 98 . Clusters were extracted only for proteins that were consistently allocated to the same clusterings (sampled from the posterior distribution) across replicates 55,99 (Supplementary Data 3).…”
Section: Marker List Generationmentioning
confidence: 99%
“…We use the implementation of Bayesian mixture models in C++ provided by Mason et al (2016). Rather than directly using a Dirichlet process (Ferguson, 1973) to infer the number of clusters or a mixture that grows and shrinks (Richardson and Green, 1997), this implementation follows the logic of Rousseau and Mengersen (2011) and Van Havre et al (2015) using an overfitted mixture model to approximate a Dirichlet process.…”
Section: Supplementary Materialsmentioning
confidence: 99%